STRENGTHENING THE ROLE OF CIVIL SOCIETY ORGANIZATIONS: ASSESSING THEIR INVOLVEMENT IN THE DECISION-MAKING OF A SOUTHERN PHILIPPINE DISTRICT. - Kate Cahimtong; Christine Tenorio (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
This article investigates the role of civil society organizations (CSOs) in the decision-making process in a district in the southern Philippines. The study used a descriptive analysis to assess CSO involvement in policy formulation, local development planning, program implementation, and monitoring and evaluation. The findings reveal that while there is limited engagement of CSOs in policy formulation, they make significant contributions to development planning, ensuring consensus-based decision-making that caters to diverse community sectors. CSOs also actively participate in program implementation and monitoring progress. However, the study admits some limitations, including a small sample size and potential redundancy of information due to statement correlation. Nonetheless, the study emphasizes the potential of CSOs to enrich the decision-making process within districts. To enhance CSO involvement, district officials should forge stronger partnerships with NGOs and private sectors, and CSOs should innovate solutions for emerging challenges. Future research should address identified limitations and involve district officials to gain a comprehensive understanding of decision-making processes.